Criminogenic Thinking Mediates the Relation Between Violent Media Exposure and Aggression. Issue 5 (27th May 2016) - Wagar, Laura; Mandracchia, Jon
ABSTRACT: For decades researchers have been exploring the connection between exposure to violent media and aggression in adolescents. In this study, we hypothesized that criminogenic thinking would mediate the relationship between violent media exposure and aggression. A sample of 382 undergraduate students completed questionnaires regarding exposure to violent media during their adolescent years, and their current endorsement of criminogenic thinking and level of aggression. Results indicated that criminogenic thinking patterns did, in fact, mediate the relationships between exposure to various forms of violent media and aggression. The implications of these findings toward a better understanding of the relationship between violent media exposure and aggressive behavior are discussed.